Market Landscape and the Role of Marketing in the Field of Mongolian Performing Arts Organizations - Ulziibadrakh, Zoljargal; Szakály, Zoltán (Anali Ekonomskog fakulteta u Subotici, 2025)
Classical music is a formal music tradition of the Western world; an accepted genre having had many positive benefits on human and animal lives. The most common benefits of classical music are to provide an immersive live experience, support psychological and physiological needs, boost our health and brain functions, and improve productivity. Many countries have a well-developed history and achievement in this field, thus an advantage, however as classical music penetrated late into Mongolian culture, it is a promising field in which to conduct research. This study aims to explore, determine, and gain insight into the marketplace as well as the role of marketing from past, current, and future perspectives as the field of classical music continues to develop in Mongolia. The study uses an in-depth interview approach with 12 interviewees including directors, marketers, managers, artists, and employees from two main Mongolian performing arts organizations, to gain a deeper understanding of this world. Based on the insights and experiences gained from these interviews, the results are identified and divided into two themes; market and audience profile, and the role of marketing within Mongolian performing arts organizations. Finally, the paper summarizes the main findings and concludes with a synopsis of key limitations and future research.